Resettable skin interfaced microfluidic sweat collection devices with chemesthetic hydration feedback - Reeder, Jonathan T.; Xue, Yeguang; Franklin, Daniel; Deng, Yujun; Choi, Jungil; Prado, Olivia; Kim, Robin; Liu, Claire; Hanson, Justin; Ciraldo, John; Bandodkar, Amay J.; Krishnan, Siddharth; et al. (Nature communications, 2019)
Recently introduced classes of thin, soft, skin-mounted microfluidic systems offer powerful capabilities for continuous, real-time monitoring of total sweat loss, sweat rate and sweat biomarkers. Although these technologies operate without the cost, complexity, size, and weight associated with active components or power sources, rehydration events can render previous measurements irrelevant and detection of anomalous physiological events, such as high sweat loss, requires user engagement to observe colorimetric responses. Here we address these limitations through monolithic systems of pinch valves and suction pumps for purging of sweat as a reset mechanism to coincide with hydration events, microstructural optics for reversible readout of sweat loss, and effervescent pumps and chemesthetic agents for automated delivery of sensory warnings of excessive sweat loss. Human subject trials demonstrate the ability of these systems to alert users to the potential for dehydration via skin sensations initiated by sweat-triggered ejection of menthol and capsaicin. Wearables capable of collecting and analyzing sweat are of interest for athletics and health monitoring. Here, the authors report a resettable microfluidic platform comprising soft pumps and valves that provides triggered release of chemesthetic agents to alert the user of excessive sweat loss.